THE ROLE OF MENTAL DEVELOPMENT OF INDONESIAN NAVY’S FIRST FLEET TO INCREASE THE OPERATION READINESS OF THE NAVY OFFICER - Sitorus, Musa Hotmatua; Suryanta, Apri; Adi, Sunarno (Jurnal Pertahanan dan Bela Negara, 2019)
Article 9 of Indonesian Law No. 34 year 2004 concerning Indonesian Defence Forces (TNI) rendering the Navy the task of maritime defense and security that requires of main equipment and weaponry system (Alutsista) such as Indonesian Warship (KRI). The Navy officer as the man who operate the warship requires a fit level of physical and mental to be able to execute the tasks optimally. One thing that is very important in maintaining and developing the mental readiness of navy officer is mental development. In the TNI Commander Decision No. Kep/940/XI/2017 dated November 21, 2017 concerning the Parental Guidelines for the TNI Mental Development Pinaka Baladika stated that the TNI mental development has a strategic role, task and function in building the capability and strength of the TNI for a strong national defense. The object of this research is the implementation of mental development in the First Fleet Command Headquarters, Indonesian Navy. The purpose of this study is to analyze the design of mental development that is conducted in the First Fleet Command Headquarters, Indonesian Navy. The analysis of the article is using role theory as the main theory which according to Levinson that roles related with three things, namely position or status, organization, and behavior. This study uses a qualitative methodology which primary data was obtained by interviews with officials at the First Fleet Command Headquarters who have duties for arranging, managing, executing, and evaluating mental development, and adding with navy officer representation. Meanwhile, secondary data was obtained by literature studies such as books, journals, magazines, letter of decisions, and etc. Data processing techniques was carried out by reducing data, presenting data, and drawing conclusions, using tools equipment NVIVO 12 plus for data coding. In this research, it was found that mental development at the First Fleet Command Headquarters had not managed its role optimally. One of the indicator is there are no position of a mental psychology officer, mental ideological officer, and mental traditional tradition officer in the organizational structure of First Fleet Command HQ. Mental development activities had not managed in accordance with the principles of modern management, especially in the planning level. Keywords: mental development, operation readines, first fleet command, Indonesian Navy, motivation.